"Us Up Here and Them Down There": How Design, Management, and Neighborhood Facilities Shape Social Distance in a Mixed-Tenure Housing Development. (September 2016) - Tersteeg, Anouk K.; Pinkster, Fenne M.
Despite the fact that social mix is an essential component of urban policies in Western Europe, it remains unclear at what spatial scale housing diversification programs may be most effective. When people with different backgrounds, household compositions, and lifestyles live in close proximity to one another, the emergence of close social ties is not always guaranteed. On the one hand, living in socially mixed environments may create bridges between residents of different social positions. On the other hand, it can lead to processes of social distancing and reproduce negative stereotypes. This article aims to provide insights into how these diverging experiences of social closeness or distance relate to place-specific features such as housing design, management practices, and the structure of local facilities. Lessons are drawn from a qualitative study on resident experiences of living with difference in a fine-grained mixed-tenure development in a newly built neighborhood in Amsterdam, the Netherlands.